HOXA cluster gene expression during osteoblast differentiation involves epigenetic control - da Silva, Rodrigo A. [UNESP] (2019)
The HOXA gene cluster is generally recognized as a pivotal mediator of positional identity in the skeletal system, expression of different orthologues conferring alternative locational phenotype of the vertebrate bone. Strikingly, however, the molecular mechanisms that regulate orthologue-specific expression of different HOXA cluster members in gestating osteoblasts remain largely obscure, but in analogy to the processes observed in acute lymphatic leukemia it is assumed that alternative methylation of HOXA promoter regions drives position specific expression patterns. In an effort to understand HOXA cluster gene expression in osteogenesis we characterize both expression and the epigenetic landscape of the HOXA gene cluster during in vitro osteoblast formation from mesenchymal precursors. We observe that osteoblast formation per se provokes strong upregulation of HOXA gene cluster expression, in particular of midcluster genes, and paradoxal downregulation of HOXA7 and HOXA10. These differences in expression appear related to promoter methylation. LnRNAs HOTAIR and HOTTIP, known to modulate HOXA expression, are also regulated by their promoter methylation processing, but do not correlate with HOXA cluster expression profile. We thus conclude that HOXA expression is profoundly regulated during osteoblast differentiation through canonical methylation-dependent mechanisms but not through the flanking lnRNAs.